2020
DOI: 10.3390/cells9010201
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of the Characteristics and Differences in Adult and Newborn Brown Adipose Tissue (BAT): Newborn BAT Is a More Active/Dynamic BAT

Abstract: Brown adipose tissue (BAT) plays an essential role in maintaining body temperature and in treating obesity and diabetes. The adult BAT (aBAT) and neonatal BAT (neBAT) vary greatly in capacity, but the characteristics and differences between them on the molecular level, as well as the related features of BAT as it develops post-delivery, have not yet been fully determined. In this study, we examined the morphological features of aBAT and neBAT of mice by using hematoxylin-eosin (H&E) staining, transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 66 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…We found that gradual cold adaptation of neonatal mice prevents programmed developmental downregulation of SLN expression in adult quadriceps and gastrocnemius, glycolytic muscles ( Pant et al, 2015a ). Neonatal mice have significant amounts of BAT with very high UCP1 expression ( Cannon and Nedergaard, 2004 ; Harris et al, 2020 ; Liu et al, 2020 ) and, therefore, it can be argued that the thermogenic demand of neonatal mice is met by BAT based NST. The finding that UCP1 −/− neonates are able to survive at 22°C (below thermoneutrality of 28°C) and can be gradually cold adapted to 4°C suggests the existence of additional NST components ( Enerback et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…We found that gradual cold adaptation of neonatal mice prevents programmed developmental downregulation of SLN expression in adult quadriceps and gastrocnemius, glycolytic muscles ( Pant et al, 2015a ). Neonatal mice have significant amounts of BAT with very high UCP1 expression ( Cannon and Nedergaard, 2004 ; Harris et al, 2020 ; Liu et al, 2020 ) and, therefore, it can be argued that the thermogenic demand of neonatal mice is met by BAT based NST. The finding that UCP1 −/− neonates are able to survive at 22°C (below thermoneutrality of 28°C) and can be gradually cold adapted to 4°C suggests the existence of additional NST components ( Enerback et al, 1997 ).…”
Section: Introductionmentioning
confidence: 99%
“…Is the same process repeated after the first exposure to cold at birth? The number and size of LDs increase during postnatal development in BAT (38) and the presence of glycogen has been described in the BAT of neonates (26,27). We can hypothesize that after the first cold exposure at birth, glycogen accumulates and is involved in the replenishment of LD in BAT.…”
Section: Discussionmentioning
confidence: 86%
“…A recent analysis compared adult and newborn BAT in mice. Several morphological and molecular differences were identified, including lncRNA expression ( Liu et al, 2020 ). For example, neonatal BAT—which seems to be more physiologically plastic and active compared to adult BAT—expresses NONMMUG024827 lncRNA.…”
Section: Lncrnas As Regulators Of Brown and Brite/beige Adipogenesismentioning
confidence: 99%